Effect of blood pressure normalization (reaching the target level) on epinephrine-induced platelet aggregation changes in patients with hypertension - V. V. Syvolap; S. P. Zhemanyuk (Zaporožskij Medicinskij Žurnal)
There is a little data about the impact of blood pressure normalization on platelet aggregation properties and the impact of antihypertensive drugs on platelet hemostasis.